Hazard Identification and Risk Assessment of PT TKA Traksi Employees - Milana Milana; Kevin Lisson Putra; Donny Fernandez; M. Yasep Setiawan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Traksi is a division of work related to transportation at PT TKA. There are cases of work accidents experienced by Traksi employees every year. This study aims to identify potential hazards from the work activities of Traksi employees. Data collection was carried out at the Koto Ubi Garden division through direct observation in the Traksi work area, and employee interviews regarding the activities carried out. The hazard identification process is carried out using the Hazard Identification and Risk Assessment (HIRA) method. From the results of hazard identification, 26 potential hazards can occur to Traksi employees. Meanwhile, from the risk assessment, there are 35% in the extreme category, 31% in the high category, 23% in the low category, and 11% in the medium category. Traksi merupakan divisi pekerjaan yang berkaitan dengan transportasi di PT TKA. Terdapat kasus kecelakaan kerja yang dialami oleh karyawan Traksi di setiap tahunnya. Penelitian ini bertujuan untuk mengidentifikasi potensi bahaya dari aktivitas kerja karyawan Traksi. Pengambilan data dilakukan pada divisi Kebun Koto Ubi melalui pengamatan langsung di area kerja Traksi, dan melakukan wawancara pekerja mengenai aktivitas kerja yang dilakukan. Proses identifikasi bahaya dilakukan dengan menggunakan metode Hazard Identification and Risk Assessment (HIRA). Dari hasil identifikasi bahaya didapatkan 26 potensi bahaya yang dapat terjadi pada karyawan Traksi. Sedangkan dari penilaian risiko terdapat 35% pada kategori ekstrim, 31% pada kategori tinggi, 23% pada kategori rendah, dan 11% pada kategori sedang.